Redesain Potensi Lokal Kewilayahan Desa Pakunden Magelang Berbasis Agro-ekowisata Pasca Konversi Lahan Terdampak Tol Jogja-Bawen - Armawi, Armaidy; Effendhy, Syafiq; Subejo; Apriliyanti, Kiki (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Land conversion for the Jogja-Bawen Toll Road has made Pakunden Village farmers survive as farmers by buying land in other villages, and some have converted to work in the tourism service sector. The tourism potential of Pakunden Village is 12 baths, 4 regional arts and the sabo dam Development Plan, which will be used as an agroecotourism site. In its dynamics, there is a difference between planning and infrastructure provided by the government. This research also aims to describe the concept of redesigning Pakunden Agro-ecotourism Village Magelang based on strengthening local wisdom as an intervention strategy for the land use change of Jogja-Bawen Toll Road. This research comprises a field study conducted in Pakunden Village, Ngluwar District, Magelang Regency, concurrently with the Adopted Village-based Community Service Program administered by the Directorate of Community Service at UGM. The research methodology employed is qualitative field research. The selection of informants in this study was based on purposive sampling, where there were considerations in the form of knowledge related to land conversion, environmental conditions of Pakunden Village and the concept of agroecotourism village development. Data collection was carried out by conducting observations, interviews, internet searches and document studies. The results of this study show that external interventions, such as the construction of sabo dam and private business opportunities through Balai Ekonomi Desa, powerfully drive the development of tourism and the local economy of Pakunden Village. However, this program is still in its initiation phase and has not been implemented in practical terms, thus the changes in the economic conditions of the community cannot be concretely depicted. Nevertheless, overall, through the sustainable development of the tourism sector, this endeavor aims to enhance rural communities and local economies.